Pre‐release evaluation of Heikertingerella sp. as a potential biocontrol agent for Tecoma stans in South Africa. (23rd October 2020) - Madire, Lulama; Simelane, David; Olckers, Terence
Abstract: Native to Central America, Tecoma stans (L.) Juss ex Kunth var. stans (Bignoniaceae) is a small tree that is invasive in South Africa and neighbouring countries. The plant was targeted for biological control in South Africa in 2003, with two insect agents released and established so far. The root‐feeding flea beetle, Heikertingerella sp. (Coleoptera: Galerucinae: Alticini), was imported from Mexico as an additional biocontrol agent and its biology and host specificity was assessed under quarantine conditions. The beetle displayed a generation time (i.e. from adult to adult) of 49 to 67 days, ensuring four annual generations under laboratory conditions. The beetle's larval and adult stages inflicted high levels of damage on the root system and the leaves of T. stans, respectively. No‐choice tests with 40 test‐plant species revealed adult feeding on only two non‐target species, Tecoma × alata and T. capensis (Thunb.) Spach, with feeding four times higher on T. stans . Larvae developed to adulthood on T. stans only. Multi‐choice tests involving the three Tecoma species confirmed these trends, demonstrating that Heikertingerella sp. is host specific. Since T . × alata is a hybrid of T. stans with invasive tendencies, any unlikely attacks by Heikertingerella sp. would be inconsequential in South Africa. The native T. capensis, which suffered little leaf damage and produced no F1 adults, is also at minimal risk of attack. We conclude that Heikertingerella sp. is a suitable biocontrol agent for T. stans and that permission for its release in South Africa be sought.